Symmetric Dimethylarginine (SDMA) as Biomarker of Chronic Kidney Diseases in Dogs - Sonu; Hariom; Kumar, Ashok; Charaya, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Chronic renal failure is the loss of the ability of kidneys to excrete waste products, concentrate urine, electrolytes and fluid balance leading to retention of creatinine, urea and other metabolic waste products in the body. The present study was planned to evaluate and correlate Symmetric Dimethylarginine (SDMA) with the severity of chronic kidney disease (CKD) and with BUN and creatinine in dogs. Twenty four dogs presented at Veterinary Clinical Complex of LLUVAS, Hisar (India), diagnosed to be suffering from renal failure on the basis of history, clinical signs and ultrasonographic findings were included in the study. The dogs were divided into three categories (atypical, mild and severe) based on the duration of presentation of cases after emergence of the clinical signs. Six apparently healthy dogs were taken for comparsion with affected ones. Serum from all the affected and apparently healthy animals was used to evaluate SDMA using ELISA kits, whereas BUN and creatinine were determined using biochemistry autoanalyzer. SDMA was significantly (20-fold) elevated in dogs suffering from renal failure as compared to the control group. Significant (p<0.01) positive correlations of SDMA with BUN and serum creatinine were found in all three categories of dogs indicating that serum SDMA can be a biomarker for detection of CKD earlier than does measurement of serum creatinine in dogs.